Impact of the Pandemic on Consumer Behavior and Business Strategy in India - Jain, Reetika (Indian Journal of Marketing, 2022)
The COVID-19 pandemic that engulfed the entire world since the beginning of 2020 forced consumers to learn the new ways of life and unlearn the existing habits within the paradigm of time flexibility but location rigidity. As consumers adapt to the ‘new normal’ of life, they embrace new digital technologies to facilitate work, study, and consumption in a more convenient manner. These newly adopted habits are visible not only at the home front but also in public places in the form of using safety gears (masks, sanitizers) and using digital platforms (to ensure social distancing). The COVID-19 protocols have led to significant disruptions in consumer behavior and consequent responses of companies in the form of their preparedness for new norms of consumer behavior. This, in turn, is posing a challenge for the future sustainability and viability of businesses, necessitating strategic changes in the business model and the marketing strategies to remain apt to consumers’ current and future needs. Companies that were unable to adjust and adapt to these sudden changes posed by the pandemic perished very soon. The present paper investigated the impact of the pandemic on the behavior of Indian consumers and their consumption habits. Though there are many studies on epidemics and pandemics, their focus is mainly on the macro-issues of the economy. The present study tried to fill this research void by analyzing the behavior of consumers in India during the pandemic, as pointed out in the market research reports by prominent research analyst firms. The paper also highlighted the implications of the changed consumer behavior for marketers in the future.